2009
DOI: 10.1302/0301-620x.91b2.21069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of asymptomatic tears of the rotator cuff

Abstract: We undertook clinical and ultrasonographic examination of the shoulders of 420 asymptomatic volunteers aged between 50 and 79 years. MRI was performed in selected cases. Full-thickness tears of the rotator cuff were detected in 32 subjects (7.6%). The prevalence increased with age as follows: 50 to 59 years, 2.1%; 60 to 69 years, 5.7%; and 70 to 79 years, 15%. The mean size of the tear was less than 3 cm and tear localisation was limited to the supraspinatus tendon in most cases (78%). The strength of flexion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 33 publications
10
132
1
5
Order By: Relevance
“…The mean age of these patients was 66 years. This is consistent with a large previously reported study of full-thickness tears in asymptomatic volunteers over 50 years of age, which showed an overall incidence of 8%, with a strong dependence on age [30].…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of these patients was 66 years. This is consistent with a large previously reported study of full-thickness tears in asymptomatic volunteers over 50 years of age, which showed an overall incidence of 8%, with a strong dependence on age [30].…”
Section: Discussionsupporting
confidence: 93%
“…However, recent studies have found that there are cases of asymptomatic RCTs in which the patient exhibits no shoulder symptoms [1][2][3][4][5][6][7][8][9][10]. It is evident that patients with symptomatic RCTs tend to demonstrate restrictions in activities of daily living (ADL); however, few reports have so far evaluated the possible restrictions of ADL in patients with asymptomatic RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Moosmayer et al [85], these three variables were found to correlate with the presence of symptoms in comparison to an asymptomatic group. The authors compared non-operative to operative treatment for smaller tears of 3 cm in size, and found a progression in tear size and structural deterioration over time, which resulted in the recurrence of symptoms and functional depreciation over time.…”
Section: Risks Of Conservative Treatment In Managing a Rotator Cuff Tearmentioning
confidence: 90%